Air pollution and gestational diabetes mellitus: evidence from cohort studies. Issue 1 (18th March 2020) - Tang, Xingyao; Zhou, Jian-Bo; Luo, Fuqiang; Han, Yipeng; Heianza, Yoriko; Cardoso, Marly Augusto; Qi, Lu
Abstract : Exposure to different air pollutants has been linked to type 2 diabetes mellitus, but the evidence for the association between air pollutants and gestational diabetes mellitus (GDM) has not been systematically evaluated. We systematically retrieved relevant studies from PubMed, Embase, and the Web of Science, and performed stratified analyses and regression analyses. Thirteen studies were analyzed, comprising 1 547 154 individuals from nine retrospective studies, three prospective studies, and one case–control study. Increased exposure to particulate matter ≤2.5 µm in diameter (PM2.5 ) was not associated with the increased risk of GDM (adjusted OR 1.03, 95% CI 0.99 to 1.06). However, subgroup analysis showed positive correlation of PM2.5 exposure in the second trimester with an increased risk of GDM (combined OR 1.07, 95% CI 1.00 to 1.13). Among pollutants other than PM2.5, significant association between GDM and nitrogen dioxide (NO2 ) (OR 1.05, 95% CI 1.01 to 1.10), nitrogen oxide (NOx ) (OR 1.03, 95% CI 1.01 to 1.05), and sulfur dioxide (SO2 ) (OR 1.09, 95% CI 1.03 to 1.15) was noted. There was no significant association between exposure to black carbon or ozone or carbon monoxide or particulate matter ≤10 µm in diameter and GDM. Thus, systematic review of existing evidence demonstrated association of exposure to NO2, NOx, and SO2, and the second trimester exposure of PM2.5 with the increased risk of GDM. Caution may be exercised while deriving conclusions from existing evidence base because of the limited number and the observational nature of studies.